Analysis of needs and teachers' perception towards business teaching materials at SMA Labschool UPI - Hanada Sabilal Khaira; M. Farid Al Hafizh; Pelangi Syaumi Alvina Darmansyah; Hafsah Nugraha; Diemas Arya Komara (Universitas Pendidikan Indonesia, 2023)
This research aims to discuss the importance of understanding teachers' perceptions of business teaching materials to enhance the quality of education. This article seeks to explore the analysis of teachers' needs and perceptions regarding business teaching materials, identify factors influencing their views, and evaluate their impact on the effectiveness of teaching and learning. The research employs a qualitative method with data collection techniques involving interviews and observations. The study results indicate that teachers' perceptions of business teaching materials are influenced by factors such as relevance, practicality, and the attractiveness of the materials. Furthermore, curriculum adjustments and teaching approaches can be implemented to meet the actual needs better, creating a dynamic and relevant learning environment for students. Therefore, this article significantly improves the quality of education at SMA Labschool UPI.